Accessing Malaysia Armed Forces Logistics System in Providing Humanitarian Logistics Support - Halizahari, M; Zain, Ruzaidin; Ismail, Ariffin; Zainol, Noor Azmi Hj Mohd; Yaacob, Safar; Che Ali, Nik Ismail Rashed (International Journal of Advanced Science Computing and Engineering, 2021)
Disasters frequently strike at any time of day or night, necessitating swift action and close coordination between various agencies. When a disaster response becomes increasingly time-consuming, the Armed Forces are frequently called in to assist. Despite the fact that disaster management is not the primary responsibility of the Armed Forces, however, the Armed Forces are frequently used as disaster response machinery because they have complete equipment, logistics, and personnel. In order to identify the logistics system available in the Malaysian Armed Forces (MAF), this study was carried out with a particular emphasis on integration and disaster management in the Armed Forces. A qualitative inquiry methodology was used to complete this study. A protocol for conducting interviews was developed and used as a guideline throughout the interview process. Snowball purposeful sampling was used in this study, which included 13 key informants from the Army, Navy, and Air Force. These individuals work in the logistics field and came from all three branches of the military. According to the findings of this study, there are no job specifications and specialisations in disaster management in the MAF. The systematic logistics management implemented by the MAF, on the other hand, has made it easier to coordinate assistance during disasters. In addition, the strength in terms of knowledge, skills and discipline portrayed by the MAF personnel showed a very high commitment to achieving disaster management objectives. This advantage is widely regarded as the most important factor in ensuring that disaster response is carried out effectively and efficiently.